Peningkatan Hasil Belajar Tematik Siswa Dengan Pendekatan Contextual Teaching and Learning (CTL) di Kelas 4 SDN 02 Percontohan Kota Bukittingi - Muniroh, Muniroh; Miaz, Yalvema (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study is to improve students' thematic learning outcomes by using a contextual teaching and learning approach. Integrated thematic learning is learning that uses themes as the main focus. The learning provides meaningful experiences to students as a whole. Said to be meaningful because in integrated thematic learning students will understand the concepts they learn through direct and real experience. This research method, using classroom action research methods. The research procedure is in the form of a cycle Each cycle consists of three stages including: planning, implementing actions, observing, and reflecting. Data collection technique through observation and tests. This data collection uses instruments in the form of observation sheets of student and teacher observations in the learning process, whereas to determine the quality of student learning outcomes used evaluation / test sheets. The results of the study show that the use of contextual teaching and learning approaches can improve students' thematic integrated learning outcomes. From the average value in the first cycle, 72.22 became 94,4 the second cycle.